Lady in Red: framing the representation of women through mise-en-scène - Napat Ruangnapakul; Norsiah Abdul Hamid (Penerbit Universiti Kebangsaan Malaysia, 2017)
Films are popular medium that can reflect and contribute to changes in cultural norms and values. The films represent reality by combining film elements with stories, expression of emotions, and creation of the expression. This study focuses on enabling audiences to view women in films through the aspects of mise-en-scène in a frame. In this study, the researchers applied close textual analysis on scenes of the main female characters in four Thai films of Bhandevanov Devakula, a Thai film director. The four selected films, namely, The Eternity, The Outrage, Jan Dara the Beginning, and Jan Dara the Finale, are samples of the study. Findings suggest that the aspects of mise-en-scène in the films constantly use the red colour in the scenes of the main female characters to show the confidence, non-innocence, or high sexual attractiveness of women. Moreover, red colour is also used to reflect the sexual desire of men. This study is significant because it facilitates understanding of the comprehensive use of each aspect of mise-en-scène. This study also provides an understanding of how mise-en-scène can frame the expression of women in films. This study also demonstrates that the textual analysis approach of a film offers a close reading to facilitate a deep understanding of the meaning of a film through the interaction of all elements. This study has implications for research on film studies, analysis of mise-en-scène, women in the media, and the film industry of Southeast Asia.